2020
DOI: 10.1021/acsmacrolett.0c00718
|View full text |Cite
|
Sign up to set email alerts
|

Reversibly Softening and Stiffening Organogels Using a Wavelength-Controlled Disulfide-Diselenide Exchange

Abstract: Wavelength-dependent light-responsive seleno-sulfide dynamic covalent bonds were used to prepare organogels with reversible changes in stiffness. The disulfide cross-link organogels prepared from norbornene-terminated poly­(ethylene glycol) (PEG-diNB) and poly­(2-hydroxypropyl methacrylate-stat-mercaptoethyl acrylate) (PEG-diNB-poly­(HPMA-stat-MEMA)) polymers underwent exchange reactions with 5,5′-diselenide-bis­(2-aminobenzoic acid) upon irradiation with UV light. Following irradiation with visible light, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
3
12
0
Order By: Relevance
“…Accordingly, the network cross-linking density could be adjusted reversibly by light. 209,210 Similar phenomena could also be observed in other hydrogel systems enabled by photoreversible [2 + 2] cycloadditions. 211,212 This strategy is only applicable for gels, and its application in dry polymers is unknown.…”
Section: Topology Isomerizable Networksupporting
confidence: 75%
See 1 more Smart Citation
“…Accordingly, the network cross-linking density could be adjusted reversibly by light. 209,210 Similar phenomena could also be observed in other hydrogel systems enabled by photoreversible [2 + 2] cycloadditions. 211,212 This strategy is only applicable for gels, and its application in dry polymers is unknown.…”
Section: Topology Isomerizable Networksupporting
confidence: 75%
“…The underlying principle is that the breaking–re-forming of the boronic ester bond is strongly influenced by the cis–trans states of the azobenzene under two different wavelengths of light. Accordingly, the network cross-linking density could be adjusted reversibly by light. , Similar phenomena could also be observed in other hydrogel systems enabled by photoreversible [2 + 2] cycloadditions. , This strategy is only applicable for gels, and its application in dry polymers is unknown.…”
Section: Topological Transformationsupporting
confidence: 57%
“…In the case of the reverse reaction under visible light irratiation, only Se−Se and S−Se bonds dissociate, leading to reformation of the initial S−S bonds. Perera and co-workers 50 prepared organogels containing disulfide bonds with the ability of reversible transformation from soft to stiff by photocontrolled Se−Se and S−S bond exchange in the presence of small molecules containing diselenide bonds, which was performed through UV light irradiation while the reverse reaction occurred under visible light irradiation. The modulus of the organogel was influenced by the irradiation wavelength, whereby the photocontrolled transformation was repeated for over five cycles and modulus recovery was 85−95% of the initial value.…”
Section: Light-responsive Homolytically Cleavable Dynamic Covalent Bondsmentioning
confidence: 99%
“…Self-healing diselenide systems have been reported as well [ 6 ]. Recently, Perera et al demonstrated that norbornene-terminated poly(ethylene glycol) and poly(2-hydroxypropyl methacrylate-stat-mercaptoethyl acrylate) polymeric hydrogels could participate in seleno-sulfide exchange reactions with 5,5′-diselenide-bis(2-aminobenzoic acid) upon irradiation with UV light, resulting in reversible hydrogel softening and stiffening [ 101 ]. Unlike the redox-reversible systems in Section 3.1.4 , which can undergo reversible sol-to-gel transitions in response to a redox stimulus, the hydrogel system described by Perera and coworkers can alter its stiffness under irradiation via seleno-sulfide exchange.…”
Section: Reaction Types and Applicationsmentioning
confidence: 99%